A STUDENTS SILENCE IN SPEAKING CLASS: FACTORS AND SOLUTIONS - Purwanti, Sri Erma; Yeni, Melda (Universitas Wiralodra, 2021)
Speaking is one of four skills that learned by the students in learning English as a foreign language. Through this skill they are supposed to be able to communicate and to express their idea, feelings, and thought orally in English. Students silence is a phenomenon that often occurs in speaking class where the students are not actively engage in speaking activity. It also happened to the eleventh grade students at SMA N.1 and SMA N.2 Tembilahan Kota. This problem motivated the researchers to investigate what factors causing the students to be silent in speaking class and what are the teachers’ efforts to cope with it. There were 144 students of eleventh grade and 5 English teachers as the subject of this research. The instruments were questionnaires, 15 closed-ended questions to the students and 10 open-ended questions for the teachers. The results shows that psychological factor is the dominant factor that make mostly students performed passively in speaking activity with percentage 42%, linguistic factor 39%, and socio-cultural 19%. While the efforts of the teachers to cope with students’ silence are implementing various strategies and teaching techniques, using audio visual media, and personal approach to help students’ difficulties in Speaking.